Effects of non-pharmacological interventions on the depressive outcomes in people with mild cognitive impairment: an overview of systematic reviews - Yaxin, Chen; Lijiao, Yan; Zhao, Chen; Ziteng, Hu; Fuqiang, Zhang; Zhenhong, Liu; Luda, Feng; Yixiang, Li; Xiangwei, Dai; Qianzi, Che; Huizhen, Li; Haili, Zhang; et al. (Frontiers in Psychiatry, 2025)
ObjectiveThis study aimed to summarize and assess the certainty of evidence of non-pharmacological interventions (NPIs) on the depressive outcomes in people with mild cognitive impairment (MCI) based on published systematic reviews (SRs).MethodDatabases including PubMed, EMBASE, PsycINFO, the Cochrane Database of Systematic Reviews, CNKI, CBM, Wanfang and VIP database were searched from their inception to June 6, 2023. The methodological quality of the SRs was evaluated using the AMSTAR2 tool, and the quality of evidence was assessed using the Grading of Recommendation Assessment, Development and Evaluation (GRADE) framework.ResultsTwelve eligible SRs were included. Three SRs focused on cognitive interventions (general, computer-based, cognitive stimulation/rehabilitation), six reviews on physical activity (Tai Chi, exercise therapy, dance), three on psychosocial interventions including cognitive behavioral therapy (CBT), mindfulness-based intervention (MBI) and type not specified, one on music therapy, and one on health education; moreover, there were two SRs on multimodal NPIs. One Cochrane SR was rated as moderate quality, while the others were rated as low quality according to AMSTAR2. The overlap between primary studies of included SRs (a total of 51 studies) was 1.8%, indicating slight overlap. General cognitive interventions (SMD=-0.25, 95% CI [−0.46, −0.04], GRADE: moderate) and computer-based cognitive interventions (narrative evidence) showed potential benefits in improving depression. Exercise therapy showed consistency between two SRs in benefiting depressive symptoms of MCI (SMD=-0.33, 95% CI [−0.56, −0.10], GRADE: Low; SMD=−0.37, 95% CI [-0.64, -0.10], GRADE: Low). Dance (SMD=−0.37, 95% CI [-1.11, 0.38], GRADE: Low), CBT (SMD=0.03,95% CI [-0.18, 0.24], GRADE: Moderate), MBI (SMD=0.29, 95% CI [0.00, 0.57], GRADE: Very Low) and health education (SMD=-0.12, 95% CI [−0.44, 0.20], GRADE: Low) did not show significant difference compared to control group in improving depressive symptoms, while the effectiveness of Tai Chi, music therapy and multimodal NPIs showed inconsistency across different studies.ConclusionCognitive interventions (general or computer-based) and exercise therapy (a type of physical activity) show preliminary potential to improve depressive symptoms, while others do not show significant effects or relate to confused effects. Further methodologically rigorous and adequately powered primary studies are necessary for each of these NPIs, with reporting on the components of the interventions clearly in MCI patients.